Comparison of fiber-reinforced composite crowns and metal ceramic crowns according to attrition of opposing teeth - Hassan, Tareq; Aurangjeb, AM (Update Dental College Journal, 2014)
Back ground: Fiber reinforcement was introduced to clinical dentistry for the first time in the 1960s when investigators attempted to reinforce polymethyl- methacrylate dentures with glass or carbon fibers. It has recently been shown that crowns, bridges and posts made of FRC can be used successfully in dental practice and they are esthetically more acceptable than conventional metal ceramic crown. Aims: A prospective comparative cross-sectional study was performed involving 60 patients who attended in the out patients department of Prosthodontics, Faculty of Dentistry, BSMMU during the period of January 2007 to December 2008. Objective: Compare fiber-reinforced composite crowns and metal ceramic crowns according to attrition of opposing teeth. Methods: Clinical data were recorded from the randomly selected 60 patients divided in to tow groups experimental and control. Attrition of opposing teeth was indexed after California Dental Associations quality evaluation system. Results: In group A patients, 12(40.0%) were male and 18(60.0%) female. In group B patients 14(46.7%) were male and 16(53.3%) were female. All the patients were in grade I in both groups after 4 months. After 8 months all patients were in grade I in group A and 29(96.7%) patients were in grade I in group B. After 12 months all patients were in grade I in group A and 28(93.3%) patients were in grade I in group B. The difference was not statistically significant (p>0.05) in chi square test. Conclusion: The Fiber Reinforced Composite crown represents a valuable development in field of Prosthetic Dentistry. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21161 Update Dent. Coll. j: 2014; 4 (1): 21-26